Social identity loss and reverse culture shock: Experiences of international students in China during the COVID-19 pandemic - Raja, Rameez; Ma, Jianfu; Zhang, Miwei; Li, Xi Yuan; Almutairi, Nayef Shabbab; Almutairi, Aeshah Hamdan (Frontiers in Psychology, 2023)
Background International students are often exposed to various challenges during life transitions. The ‘mindsponge’ mechanism suggests that individuals absorb and integrate new cultural values that are compatible with their core values while rejecting those of lesser importance. On the basis of this notion, this article explores the experiences of international students in China regarding their unplanned return to their home countries during the COVID-19 pandemic through the lens of the mindsponge mechanism. Aim This article aims to highlight the experiences of international students in China who are going through life transitions due to the global pandemic. The study focuses on the experiences of two groups of international students: (1) Those who remained in China during the pandemic, and (2) those who had left China and were stranded in their home countries due to a ban on international travel amid COVID-19. Method This qualitative study comprised of in-depth semi structured in-person and online interviews. Thematic Analysis was used to analyze the data in order to generate study themes. Results The results revealed that students who remained in China experienced challenges which included anxiety, closure of campuses, lockdown, their parents’ concern regarding health issues, and not being able to meet with friends. On the other hand, students who had left China during the pandemic were confined to their home countries. This group of students experienced more severe problems than the students who remained in China. Since the transition to home countries was “unplanned,” they were not ready to readjust to their native culture and were vulnerable to severe reverse culture shock. Upon returning to their home countries, international students faced a number of challenges, including readjustment to their home countries and changes in their lives in host and home countries. In addition, they lost social and academic resources, such as the disruption of study environment, losing important group memberships, financial constraints, visa expiry, graduation delay, and academic suspension. Conclusion This study concluded that the international students experienced cultural problems after unplanned transition to their home countries during the pandemic. They described effects of reverse culture shock as being more distressing. They perceived dissatisfaction due to loss of previously held social identities and sense of belonging to the traditional society they left behind. There is a need of future studies on the long-term effect of unplanned transition on psychological, social and professional experiences. The process of readjustment has proven to be a challenging endeavor.